Quality of Human Resources at the Secretariat of the Regional Representative Council of Palu City - Yulianti Pakiding; Hartawan; Intam Kurnia; Nuraisyah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The research investigates the quality of apparatus resources at the Secretariat of the Palu City Regional People's Representative Council, focusing on both theoretical and practical implications. The study employs a qualitative descriptive method, with data collected through interviews with four informants, field observations, and document analysis. The analysis used is Sedarmayanti's Human Resources theory which includes six aspects: planning and analysis, opportunity, appointment, resource development, allowances, and inter-official relations. Findings indicate that planning and analysis, as well as resource development, are relatively low, while opportunity and appointment are considered good but require careful consideration. Allowances and inter-official relations are found to be adequate, with good communication among officials. Recommendations include enhancing training, education, and compensation systems to improve apparatus resource quality